2001
DOI: 10.1007/s004210100386
|View full text |Cite
|
Sign up to set email alerts
|

Muscle enzyme adaptation to training and tapering-off in spinal-cord-injured humans

Abstract: The activity of muscle metabolic enzymes depends on the amount and type of physical training. We examined muscle enzyme adaptation to prolonged training followed by a period of lowered activity in spinal-cord-injured individuals (SCI). Ten SCI [mean age 35 (SEM 2) years, mean body mass 78 (SEM 4) kg, mean time post-injury 12 (SEM 2) years and range of lesion C5-T4] were given 12 months of functional electrical stimulation of an upright cycling motion for 30 min a day, three times a week, followed by 6 months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our finding that the oxidative capacity after cSCI is impaired is in concurrence with in-vivo and in vitro models of complete SCI in both humans (Kjaer, Mohr et al 2001) and animal models (Gregory, Vandenborne et al 2003). In-vitro studies show that mixed muscles such as the gastrocnemius and the vastus lateralis have significantly lower mitochondrial enzyme activity following spinalization in both cats and rats (Jiang, Roy et al 1991; Gregory, Vandenborne et al 2003).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our finding that the oxidative capacity after cSCI is impaired is in concurrence with in-vivo and in vitro models of complete SCI in both humans (Kjaer, Mohr et al 2001) and animal models (Gregory, Vandenborne et al 2003). In-vitro studies show that mixed muscles such as the gastrocnemius and the vastus lateralis have significantly lower mitochondrial enzyme activity following spinalization in both cats and rats (Jiang, Roy et al 1991; Gregory, Vandenborne et al 2003).…”
Section: Discussionsupporting
confidence: 80%
“…Drastic declines in mitochondrial enzyme activity, capillary density and a shift in fiber type composition to type II glycolytic fibers of the paralyzed skeletal muscles is well documented after complete SCI in humans (Kjaer, Mohr et al 2001) and in spinalized animal models (Jiang, Roy et al 1991; Durozard, Gabrielle et al 2000; Gregory, Vandenborne et al 2003). Skeletal muscle metabolic dysfunction has the potential to decrease oxidative capacity and to negatively impact muscle fatigability (Wang, Hiatt et al 1999; Bhambhani, Tuchak et al 2000; McCully, Mulcahy et al 2011; Erickson, Ryan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The inability to find increases in citrate synthase activity in the dynamically trained leg was unexpected given a previous study indicating that changes in muscle enzymes are unrelated to exercise performance or the magnitude of sympathoadrenergic drive 20. Earlier studies using dynamic‐based exercise have reported increases in citrate synthase activity in the vastus lateralis muscle of up to 160% after 4, 8, and 10 weeks of electrical stimulation–induced cycling 7, 9, 22.…”
Section: Discussionmentioning
confidence: 96%
“…Eight weeks of FES cycling resulted in an increase in citrate synthase, a marker of mitochondrial mass[ 61 ]. Similarly, studies found increased citrate synthase as well as increased function of enzymes involved in glycolysis and β-oxidation[ 62 , 63 ]. Finally, SDH was increased after 4 wk of training, suggesting that complex II activity is increased with exercise[ 64 ].…”
Section: Mitochondrial Health Status After Scimentioning
confidence: 99%